2018
DOI: 10.1159/000496000
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Agents in IgA Nephropathy: An Update Network Meta-Analysis

Abstract: Background/Aims: The present network meta-analysis of randomized controlled trials (RCTs) was to explore the efficacy and safety of different pharmacologic interventions in IgA nephropathy with proteinuria more than 0.75 g/d. Methods: We systematically searched the Cochrane Library, Embase, and PubMed database for studies compared the rate of clinical remission and/or serious adverse events in IgA nephropathy patients with proteinuria (> 0.75 g/d) up to August 1, 2018. We ranked the comparative effects of all … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…Hou and colleagues 4 proposed that among RASB + CS had lower risks for worse renal function and long-term renal protection. 7 In our study, the eGFR of only one patient decreased >30% compared with the baseline in the half CS + RASB group, while three patients were observed in the full CS group during the observation period. No patients progressed to ESRD or required renal replacement therapy.…”
Section: Discussionmentioning
confidence: 39%
See 2 more Smart Citations
“…Hou and colleagues 4 proposed that among RASB + CS had lower risks for worse renal function and long-term renal protection. 7 In our study, the eGFR of only one patient decreased >30% compared with the baseline in the half CS + RASB group, while three patients were observed in the full CS group during the observation period. No patients progressed to ESRD or required renal replacement therapy.…”
Section: Discussionmentioning
confidence: 39%
“…Several RCTs that have tested the efficacy of a CS regimen compared with a no CS control in IgAN found that full-dose CS resulted in better clinical outcomes in terms of remission and long-term outcomes. 1214 The network meta-analysis, 7 that included patients with IgAN with 24 h UP >0.75 g/d, demonstrated that RASB + CS was the most effective treatment to prevent ESRD or the doubling of Scr, was effective in reducing proteinuria, and strongly supported the efficacy and long-term renal protective value of RASB + CS treatment.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Statistics have been applied to determine significant predictors for the diagnosis or classification of various diseases [8] . Subsequently, different statistical algorithms, biological datasets, and parameters may result in different outputs.…”
Section: Introductionmentioning
confidence: 99%
“…This study was conducted according to the PRISMA protocols (15)(16)(17)(18)(19). We systematically searched PubMed, Google Scholar, Embase, and Cochrane Library, as well as China National Knowledge Infrastructure (CNKI), a key national research and information publishing institution in China, for articles up to August 31, 2020, with the restriction of language to English and Chinese.…”
Section: Literature Searchmentioning
confidence: 99%